Characterization and Comparative Evaluation of a Novel PAI-1 Inhibitor - Gils, Ann; Stassen, Jean-Marie; Nar, Herbert; Kley, Joerg T.; Wienen, Wolfgang; Ries, Uwe J.; Declerck, Paul J. (Thrombosis and Haemostasis, 2002)
Plasminogen activator inhibitor-1 (PAI-1), the primary physiological inhibitor of both tissue-type plasminogen activator and urokinasetype plasminogen activator in plasma, is a well established risk factor in thrombotic diseases. Reduction of active PAI-1 levels may lead to a decreased tendency of thrombosis. Compounds that can suppress pharmacologically active PAI-1 levels are therefore considered as putative drugs.In the present study, we describe the PAI-1 neutralizing properties and mechanism of a newly selected compound (i. e. fendosal, HP129) in comparison to four previously reported compounds (i. e. AR-H029953XX, XR1853, XR5118 and the peptide TVASS) using different assays. The inhibitory effect of these compounds on active PAI-1 was analyzed by a plasmin-coupled chromogenic assay (Coaset® t-PA), direct chromogenic assays (t-PA, u-PA) and quantification of complex formation by ELISA, SDS-PAGE and surface plasmon resonance. Comparative evaluation of the obtained IC50 values reveals large differences [i. e. IC50 of 15 µM (HP129) vs. >1000 µM (XR5118) determined at 37° C using SDS-PAGE] between the compounds studied.Importantly, the relative potency of the various compounds is also dependent on the method used (10 to 170-fold differences in IC50 values). Characterization of the PAI-1 forms (i. e. active, non-reactive and substrate) generated upon inactivation reveals that the newly described compound HP129 induces a unique pathway (i. e. active to non-reactive conversion via a substrate-behaving intermediate) of inactivation compared to the other compounds.Taken together, these data strongly suggest that the various compounds act through different mechanisms. In addition, the results stress the necessity for a careful selection of the method used for the evaluation of PAI-1 inhibitors, preferably requiring a panel of screening methods.
Keywords: PAI-1; PAI-1 inhibitor; serpin; thrombosis